Pengaruh Model Pembelajaran Discovery Learning berbasis Pendekatan STEAM terhadap Keterampilan Proses Sains Siswa Materi Sistem Koordinasi di SMA Negeri 1 Tapa: (The Effect of Discovery Learning Model based on STEAM Approach on Students Science Process Skills on Coordination System Material at SMA Negeri 1 Tapa) - Mantulangi, Sri Nanang; Solang , Margaretha; Akbar , Muh. Nur; Lamondo , Djuna; Husain , Ilyas H.; Jannah , Magfirahtul (BIODIK, 2025)
STEAM-based discovery learning model can train students to find their own information and knowledge based on the results obtained through their observations. This study aims to determine the effect of STEAM-based discovery learning model on students' science process skills on coordination system material. The research method used is a quantitative approach. With the type of quasi experiment research and using the Two Group Pretest-Postest Design design. Before being given treatment, the sample was first given a Pretest (initial test) and when after being given treatment then given a Posttest (final test). The results showed that the results of the N-Gain test in the experimental class showed an average value of 0.63 and included a moderate category. While the results showed the results of the N-Gain test in the control class showed the average value of 0.43 and included the moderate category, the conclusion of this study is that there is an effect of the STEAM-based discovery learning model on science process skills. Abstrak. Model Discovery Learning berbasis STEAM dapat melatih siswa untuk menemukan sendiri informasi dan pengetahuannya berdasarkan hasil yang diperoleh melalui pengamatannya. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Discovery Learning berbasis STEAM terhadap keterampilan proses sains siswa pada materi sistem koordinasi. Metode penelitian yang dilakukan adalah Pendekatan Kuantitatif. Dengan jenis penelitian quasi eksperimen dan menggunakan desain Two Group Pretest-Postest Design. Sebelum diberikan perlakuan, terlebih dahulu diberi sampel Pretest (tes awal) dan pada saat sesudahnya diberi perlakuan kemudian diberikan Posttest (tes akhir). Hasil penelitian menunjukkan bahwa hasil uji N-Gain pada kelas eksperimen menunjukkan hasil nilai rata-rata adalah 0.63 dan termasuk kategori sedang. Sedangkan hasil penelitian menunjukkan hasil uji N-Gain pada kelas kontrol menunjukkan hasil nilai rata-rata adalah 0.43 dan termasuk kategori sedang, Kesimpulan dari penelitian ini adalah terdapat pengaruh model pembelajaran Discovery Learning berbasis STEAM terhadap keterampilan proses sains.